2021
DOI: 10.1063/5.0042560
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-hydrodynamic pulsations in simple batch A + B → C systems

Abstract: Spatio-temporal oscillations can be induced under batch conditions with ubiquitous bimolecular reactions in the absence of any nonlinear chemical feedback, thanks to an active interplay between the chemical process and chemically driven hydrodynamic flows. When two reactants A and B, initially separated in space, react upon diffusive contact, they can power convective flows by inducing a localized variation of surface tension and density at the mixing interface. These flows feedback with the reaction-diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…When chemically‐induced surface tension gradients are beyond a critical threshold, the resulting flows undergo an oscillatory instability which entrains the dynamics of the chemical fields. As a whole, the phenomenon presents then an intrinsic hydrodynamic nature, [57] similar to the well‐known cases where Marangoni flows and related oscillations are promoted through an external fixed spatial gradient of temperature [16] …”
Section: Minimal Ingredients For Chemohydrodynamic Oscillationsmentioning
confidence: 72%
See 4 more Smart Citations
“…When chemically‐induced surface tension gradients are beyond a critical threshold, the resulting flows undergo an oscillatory instability which entrains the dynamics of the chemical fields. As a whole, the phenomenon presents then an intrinsic hydrodynamic nature, [57] similar to the well‐known cases where Marangoni flows and related oscillations are promoted through an external fixed spatial gradient of temperature [16] …”
Section: Minimal Ingredients For Chemohydrodynamic Oscillationsmentioning
confidence: 72%
“…This idea of chemo‐hydrodynamic scenarios as a further example of rudimentary mechanisms for the emergence of functional and evolutionary behaviours has to be substantiated through experiments, starting from proof‐of‐concept systems where these dynamics can be isolated by taking into account the minimal ingredients described in previous sections, i. e., the localisation of the reactive source, that has to sustain a large surface‐tension gradient. In a recent paper, [57] we have suggested that labscale model systems may rely on hydrolysis, dissolution or photochemical processes that might also include thermal contributions. In particular, chemo‐Marangoni‐driven oscillations could be obtained in very shallow quasi‐2D reactors (or in microgravity flights) through endothermic processes such as the endothermic alkyl‐formate hydrolysis [70] or dissolution of salts like NH 4 NO 3 , since decreasing temperature is normally associated with an increase in the surface tension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations